SHORT STORY AS A MEDIA FOR MOTIVATING STUDENTS' IMPROVEMENT IN READING - Dwi Indah Pratiwi; Juita Putri; Agung Suhadi (Premise: Journal of English Education and Applied Linguistics, 2020)
This study informs the use of short story as media for motivating students improvement in reading that is tested in third semester B class at Muhammadiyah University of Bengkulu, based on research in EFL students classrooms state, a good indicator of improved motivation and interest in reading can be used by the short story (Ceylan,2016). This method in this research used experimental methods, based on the research conducted. The result showed there was an improvement in students motivation in reading. The mean score of the pre-test was 67,64. Then the mean score of the post-test is 94,11. There was an improvement in students scores between pre-test and post-test, it is improved 39,13%. It means the result of the test was satisfactory and show the best achievement. So, it can be concluded that improving students motivation in reading by using short stories as media is improved. It means that this technique can be used by other researchers to improve the same reading skill.